ASME 2007 Energy Sustainability Conference 2007
DOI: 10.1115/es2007-36080
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Residential Energy Assistance

Abstract: This paper describes a four-step method to analyze the utility bills and weather data from multiple residences to target buildings for specific energy conservation retrofits. The method is also useful for focusing energy assessments on the most promising opportunities. The first step of the method is to create a three-parameter changepoint regression model of energy use versus weather for each building and fuel type. The three model parameters represent weather independent energy use, the building heating or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…The next step in the process was to normalize electricity use data for each residence by dividing by the square footage. Both the natural gas and electricity consumption over the noted time periods of each data set were analyzed using Energy Explorer software (Raffio et al, 2007), which allows a weather normalization of the energy consumption. In Figs.…”
Section: Case Study-yellow Springs Ohio Consumption Patternsmentioning
confidence: 99%
“…The next step in the process was to normalize electricity use data for each residence by dividing by the square footage. Both the natural gas and electricity consumption over the noted time periods of each data set were analyzed using Energy Explorer software (Raffio et al, 2007), which allows a weather normalization of the energy consumption. In Figs.…”
Section: Case Study-yellow Springs Ohio Consumption Patternsmentioning
confidence: 99%
“…The statistical models relate unique contributions of various factors to residential energy consumption. Raffio, Isambert, Mertz, Schreier, & Kissock (2007) linearly associated housing units, socio-economic, and demographic features of households and weather data with residential energy profile. Fung, Aydinalp, & Ugursal (1999) showed that residential energy consumption is linearly correlated with energy price, household demographics, appliance features, and weather, across different end-uses.…”
Section: Prior Studiesmentioning
confidence: 99%
“…Most regression models have been found to be linear and of the first order due to the thermodynamic principles of energy flow in buildings and the simplicity of the statistics involving the formulation of the linear models [6]. These types of models have been commonly used in both commercial and residential analysis [7][8][9][10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The objective of this investigation is to examine the effectiveness of simple inverse linear statistical regression models for establishing baseline energy consumption models for industrial manufacturing facilities, and to use these models to disaggregate energy consumption into dependence on production, weather, or independence from both. Extensive research using regression analysis or calibrated building simulations has been performed in order to create baseline energy consumption models for residential buildings and commercial institutions [2,[7][8][9][10][11][12][13]. However, few attempts have been made to discuss the applicability of these methodologies to generate baseline energy consumption models for industrial manufacturing facilities [14][15][16].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation